Australian Saltmarsh Ecology - Editors Saintilan, Neil (Collingwood CSIRO Pub., 2009)
"Australian Saltmarsh Ecology presents the first comprehensive review of the ecology and management of Australian saltmarshes. The past 10 years in particular have seen a sustained research effort into this previously poorly understood and neglected resource. In 10 chapters contributed by experts in each discipline, the book outlines what is known of the biogeography and geomorphology of Australian saltmarshes, their fish and invertebrate ecology, the use of Australian saltmarshes by birds and insectivorous bats, and the particular challenges of management, including the control of mosquito pests, and the issue of sea-level rise. It provides a powerful argument that coastal saltmarsh is a unique and critical habitat vulnerable to the combined impacts of coastal development and sea-level rise."
Include Color Illustration and Index
Keywords: Salt marsh ecology -- Salt marshes -- Australia